A kinome-wide RNAi screen identifies ALK as a target to sensitize neuroblastoma cells for HDAC8-inhibitor treatment. Issue 12 (December 2018) - Shen, Jing; Najafi, Sara; Stäble, Sina; Fabian, Johannes; Koeneke, Emily; Kolbinger, Fiona; Wrobel, Jagoda; Meder, Benjamin; Distel, Martin; Heimburg, Tino; Sippl, Wolfgang; Jung, Manfred; et al.
Abstract The prognosis of advanced stage neuroblastoma patients remains poor and, despite intensive therapy, the 5-year survival rate remains less than 50%. We previously identified histone deacetylase (HDAC) 8 as an indicator of poor clinical outcome and a selective drug target for differentiation therapy in vitro and in vivo. Here, we performed kinome-wide RNAi screening to identify genes that are synthetically lethal with HDAC8 inhibitors. These experiments identified the neuroblastoma predisposition geneALK as a candidate gene. Accordingly, the combination of the ALK/MET inhibitor crizotinib and selective HDAC8 inhibitors (3–6 µM PCI-34051 or 10 µM 20a) efficiently killed neuroblastoma cell lines carrying wildtypeALK (SK-N-BE(2)-C, IMR5/75), amplifiedALK (NB-1), and those carrying the activatingALK F1174L mutation (Kelly), and, in cells carrying the activating R1275Q mutation (LAN-5), combination treatment decreased viable cell count. The effective dose of crizotinib in neuroblastoma cell lines ranged from 0.05 µM (ALK -amplified) to 0.8 µM (wildtypeALK ). The combinatorial inhibition of ALK and HDAC8 also decreased tumor growth in anin vivo zebrafish xenograft model. Bioinformatic analyses revealed that the mRNA expression level ofHDAC8 was significantly correlated with that ofALK in two independent patient cohorts, the Academic Medical Center cohort (n = 88) and the German Neuroblastoma Trial cohort (n = 649), and co-expression of both target genes identified patients with very poor outcome. Mechanistically, HDAC8 and ALK converge at the level of receptor tyrosine kinase (RTK) signaling and their downstream survival pathways, such as ERK signaling. Combination treatment of HDAC8 inhibitor with crizotinib efficiently blocked the activation of growth receptor survival signaling and shifted the cell cycle arrest and differentiation phenotype toward effective cell death of neuroblastoma cell lines, including sensitization of resistant models, but not of normal cells. These findings reveal combined targeting of ALK and HDAC8 as a novel strategy for the treatment of neuroblastoma.